Fractographic approach to metallurgical coke failure analysis. Part 2: Cokes from binary coal blends. (15th September 2016) - Roest, Richard; Lomas, Hannah; Mahoney, Merrick R.
Highlights: Failure profiles were constructed for cokes from single coals and binary blends. Fractography was used to examine and quantify the coke breakage behaviour. Non-linear effects were seen in the breakage behaviour of cokes from binary blends. The grain boundaries have a significant effect on the metallurgical coke strength. Abstract: Metallurgical coke used in blast furnaces is the result of blending coals to achieve the optimum coke strength properties. Prediction of coke strength from coal properties relies primarily on statistical methods. Improvement of these models is desirable. We believe a better understanding of the fundamental factors controlling coke strength is required to achieve this. In this second of a series of three papers, we apply our recently developed fractographic approach to examine and quantify the breakage behaviour and microstructural weaknesses in pilot oven metallurgical cokes from two series of single coals and binary blends of the coals. We have successfully applied fractography to perform an effective failure analysis of the complex, heterogeneous coke material. Summaries of the factors contributing to the failure of each coke studied have been presented as radar graphs. These graphs demonstrate that the failure profile of the cokes from blends is not simply a weighted average of the fracture behaviour of the cokes from the constituent single coals. Instead, non-additive effects are observed, and this may have implications for the mathematical models widely used to predict coke behaviour and strength in the blast furnace. Trends between the various fractographic parameters have been identified, and preliminary relation of these to both the maximum compressive strength of each coke and basic properties of the original coals, has been completed. Enhanced understanding of how the fracture behaviour of each coke relates to the properties of the coal blend used will help facilitate better prediction of coke strength from coal properties and ultimately optimisation of the coal blending process.